2010
DOI: 10.1590/s1517-70762010000200006
|View full text |Cite
|
Sign up to set email alerts
|

Diameter dependence of tensile strength by Weibull analysis: Part III sisal fiber

Abstract: Environmental aspects and economical advantages are motivating the use of natural fiber as reinforcement of polymer composites in substitution for synthetic fiber composites such as fiber glass. In particular, the sisal fiber is one of the most investigated and being used in engineering systems. By contrast to synthetic fibers, natural fibers have the disadvantage of being heterogeneous in their dimensions specially the diameter. In several natural fibers it has been found that the smaller the diameter, the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 10 publications
2
23
0
2
Order By: Relevance
“…The already mentioned recent works [10][11][12][13][14][15][16][17][18][19] on the tensile strength variation with the LCF equivalent diameter showed a consistent inverse correlation similar to what was earlier reported on pineapple. [4,8] Consequently, very thin diameter LCFs could eventually be selected with relatively high strength.…”
Section: High-strength Lcfssupporting
confidence: 79%
See 2 more Smart Citations
“…The already mentioned recent works [10][11][12][13][14][15][16][17][18][19] on the tensile strength variation with the LCF equivalent diameter showed a consistent inverse correlation similar to what was earlier reported on pineapple. [4,8] Consequently, very thin diameter LCFs could eventually be selected with relatively high strength.…”
Section: High-strength Lcfssupporting
confidence: 79%
“…[10][11][12][13][14][15][16][17][18][19] The statistical distribution of diameters was based on 100 randomly picked fibers from the lots. For each type of fiber overviewed in the PW, histograms corresponding to the frequency of diameter distribution were obtained [10][11][12][13][14][15][16][17][18][19] and reproduced in Figure 3. Diameters and cross-sectional areas along the fiber length were evaluated by means of profile projector measurements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The small diameter of fibre at 5 wt. % untreated GSP-PLA nanofibre can also be said to contribute to its high UTS and energy at break as observed in Figures 1 and 5 [15,16]. The composite with 3 wt.…”
Section: Methodsmentioning
confidence: 96%
“…These parameters are greatly influenced by the climate condition, growth age, source and the digestion process, which in turn influence the properties of fiber and it's composite 5,6 . It has been reported that fiber strength increases with increasing cellulose content and decreasing spiral angle in micro level 5 , and shows inverse dependence on diameter of fiber form macro view 7,8 . However, how growing point influences the properties of fiber has not been reported.…”
Section: Introductionmentioning
confidence: 98%